Eudistomins A-Q, .beta.-carbolines from the antiviral Caribbean tunicate Eudistoma olivaceum - Rinehart, Kenneth L; Kobayashi, Junichi; Harbour, Gary C; Gilmore, Jeremy; Mascal, Mark; Holt, Tom G; Shield, Lois S; Lafargue, Francoise (Journal of the American Chemical Society, 1987)
Seventeen eudistomins have been isolated from the Caribbean colonial tunicate Eudistoma olivaceum. Twelve are .beta.-carbolines-four of them (eudistomins D, J, N, and O) unsubstituted at C-1, three (A, B, and M) with pyrrol-2-yl substituents at C-1, and five (G, H, I, P, and Q) with 1-pyrrolin-2-yl substituents at C-1; five (eudistomins C, E, F, K, and L) are 1,2,3,4-tetrahydro-.beta.-carbolines with an oxathiazepine ring fused at C-1 and N-2. Syntheses are described of eudistomins D, H, I, M, N, O, and Q and of two related compounds. The major route to both 1-(pyrrol-2-yl)- and 1-(1-pyrrolin-2-yl)-substituted eudistomins proceeded through Grignard addition of 2-(1,3-dioxa-2-cyclohexyl)ethyl bromide to 1-cyano-substituted .beta.-carbolines, followed by appropriate cyclization, reduction, and dehydrogenation.